REVIEW PERBEDAAN PERSEPSI MASYARAKAT PULAU BELITUNG TERHADAP IKAN CEMPEDIK (Osteochilus spilurus) - Ardiansyah Kurniawan; Ira Triswiyana (Universitas Muhammadiyah Gresik, 2021)
Cempedik fish (Osteochilus spilurus) is a local fish of Belitung Island that has important economic value in East Belitung but not so in western Belitung. This difference is interesting to compare the perception of the people of West Belitung and East Belitung towards Cempedik Fish. The majority of people in both regions know and consume Cempedik fish. The difference occurs in the way consumers get to fish with the majority in East Belitung getting it from purchases, while most consumers in West Belitung get it from independent fishing. Cempedik consumption patterns are more influenced by the culture of the local community. Cempedik's fishing season in East Belitung is considered to be in the rainy season, while in West Belitung it is in the dry season. The ethno-technology of fishing in the two areas is also different from passive fishing gear in East Belitung and active gear in other areas. Exploitation in large numbers in East Belitung makes the community perceive a decrease in the size and number of Cempedik's catch from year to year so it needs to be domesticated.